Finite Element Rail Vibration Dynamics - Ground Improvement with Lime-Cement Columns - Berg, Sebastian; Larsson, Martin (My University, 2005)
Ground vibrations from trains are a major problem for people living close to railway lines. When a high-speed train passes at an embankment constructed on soft soils resonance effects can appear and cause high amplitude vibrations for the surrounding environment. To design appropriate railways without expensive costs on field tests it is important to create models and simulate the effects of countermeasures for the embankment and the surrounding soil. In this thesis countermeasures with Lime-Cement Columns have been integrated into a 3D FEM90 train-induced ground vibration model developed by the Computational Dynamics Group at Chalmers. Three types of configurations of Lime-Cement Columns have been studied: 1. A case with columns straight under the rails (LC-Column Model). 2. Leaning columns under the embankment (LLC-Column Model). 3. Barrier, where the columns is placed outside the embankment. The column configurations has been evaluated and compared when an X2000 train pass in velocities between 140 km/h and 300 km/h. The effect of the angle for the leaning columns has been evaluated as well as the influence of the diameter and the strength of the columns. At the track the simulations demonstrate the importance with columns near the rail when reducing dynamic amplifications at the track. The simulations also show that the effect of the countermeasures in the soil is dependent of the critical velocity of the system. For low train velocities below the critical the columns straight under the track is the most effective. At higher velocities the leaning columns works better regarding the vertical amplitude in the soil. The leaning column angle shows that a higher angle has good effect at the track. In the soil a high angle has opposite effect.
Keywords: Samhällsbyggnadsteknik; Civil Engineering